Narkolema pada Media Hiburan Drama Korea - Wulandari, Dita Risky Dwi; Ruja, I Nyoman; Ratnawati, Nurul (Universitas Negeri Malang, 2024)
In today's digital era, the threat of moral damage to teenagers is not only caused by drinking, narcotics, but also narkolema. Narkolema is defined as human addiction to watching or accessing pornography through the eyes. This study aims to: (1) analyze pornographic scenes in Korean dramas, (2) analyze the causes and effects of addiction to watching pornographic scenes in Korean romance dramas. This study uses a qualitative approach and a descriptive research type as a methodological basis. Data collection was carried out on college students from Malang who are students. This research was obtained from primary and secondary data. Research data collection techniques are observation, interviews, and documentation. The results of this research show that there are scenes that are considered pornographic in the Korean romance drama entitled Fanta G Spot and Nevertheless, namely bed scenes that show uncovered breasts and buttocks, masturbation activities, and similar relationships. The causes of college students watching pornographic scenes in Korean romance dramas include storylines that are packaged attractively and dynamically played by beautiful characters, looking for entertainment to get rid of boredom from the routine they live in, getting references such as education on relationship behavior with the opposite sex, feeling happier after watching, as well as sexual education. As a result, the perception of adolescents with pornographic aspects found in Romance Drakor becomes two opinions or two points of view. The first opinion is positive that accepts the existence of pornographic aspects in Romance Drakor as part of the elements of entertainment, art and education and does not view these pornographic aspects as elements that can have a negative impact. The second opinion is a negative point of view that accepts the existence of pornographic aspects in Romance Drakor that are considered to be part of the elements of the storyline which are packaged beautifully and cinematically and can have a negative impact with a different percentage for each individual watching. Di era digital saat ini, ancaman kerusakan moral remaja tidak hanya disebabkan oleh minum-minuman keras, narkotika, namun juga narkolema. Narkolema diartikan sebagai kecanduan manusia menonton atau mengakses pornografi lewat mata. Penelitian ini bertujuan untuk (1) Menganalisis adegan pornografi dalam drama korea , (2) Menganalisis sebab dan akibat kecanduan menonton adegan pornografi drama korea romance. Penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian deskriptif yang digunakan sebagai landasan metodologis. Pengambilan data dilakukan di kota malang pada mahasiswa. Penelitian ini didapat dari data primer dan sekunder. Teknik pengumpulan data penelitian dengan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukan bahwa terdapat adegan yang termasuk pornografi dalam drama korea romance dengan judul Fanta G Spot dan Nevertheless yaitu adegan ranjang yang memperlihatkan buah dada dan pantat tanpa penutup, kegiatan masturbasi, serta hubungan sejenis. Penyebab mahasiswa menonton adegan pornografi dalam drama korea romance diantaranya yaitu jalan cerita yang dikemas menarik dan tidak monoton ditambah lagi tokohnya yang rupawan, mencari hiburan untuk menghilangkan kejenuhan dari rutinitas yang mereka jalani, mendapatkan referensi ilmu seperti edukasi perilaku relationship dengan lawan jenis, merasa lebih happy setelah menonton, serta edukasi seksual. Akibat dari mahasiswa menonton drama korea romance terdapat aspek pornografi yang ada pada drakor romance. Terbagi menjadi dua pendapat atau dua sudut pandang yaitu yang pertama sudut pandang positif yaitu pornografi sebagai unsur hiburan, edukasi, dan seni yang dalam artian pendapat menerima keberadaan pornografi dalam drakor romance dan tidak memandang pornografi memberikan dampak negatif. Kedua adalah memandang bahwa pornografi memberikan dampak negatif dengan persentase yang berbeda tiap personal yang menonton. Pendapat menerima keberadaan pornografi dalam drakor romance dan menganggap pornografi bagian dari unsur alur cerita yang dikemas secara sistematik dan indah.